Methylprednisolone pulse therapy for critically ill patients with coronavirus disease 2019: A single‐center retrospective observational study. Issue 1 (6th September 2022) - Okano, Hiromu; Furuya, Ryosuke; Niida, Shoko; Minami, Sakura; Horiuchi, Hiroshi; Suzuki, Naoya; Otsuka, Tsuyoshi; Miyazaki, Hiroshi
Abstract : Aim: This study compared the clinical outcomes of critically ill patients with coronavirus disease (COVID‐19) pneumonia treated with high‐dose methylprednisolone and other steroids. Methods: This retrospective observational study included critically ill COVID‐19 pneumonia adult patients with tracheal intubation treated between April 1, 2020, and September 15, 2021. Of the 46 patients who met the inclusion criteria, 36 received steroid pulse therapy (Group P) and 10 received steroids without pulse therapy (Group NP). Subgroup analyses in Group P by methylprednisolone dose of 1000 or 500 mg for 3 days during intensive care unit stay were carried out. The primary and secondary outcomes were 28‐day mortality and steroid‐associated complications, respectively. Results: In the Kaplan–Meier curve analysis, there was no difference in the 28‐day survival between P and NP groups (log–rank P  = 0.046). Univariate Cox proportional hazard model also showed that Group P had a decreased 28‐day mortality (hazard ratio 0.30; [95% confidence interval, 0.20–0.44]; P  < 0.01). After adjusting for covariates (age, sex, remdesivir, baricitinib, and favipiravir), using the multivariate Cox proportional hazards model, Group P had improved 28‐day mortality (0.50 [0.30–0.85], P  = 0.01). Conclusion: Steroid pulse therapy might improve the 28‐day and in‐hospital mortality in critically ill patients with COVID‐19 pneumonia. Abstract : In the Kaplan–Meier curve analysis, there was no difference in 28‐day survival between the P and NP groups (log rank P  = 0.046). However, in univariate analysis using Cox proportional hazard model, steroids pulse therapy decreased the risk of death in critically‐ill patients with COVID‐19 pneumonia (hazard ratio [HR]: 0.30, 95% confidence interval [CI]; 0.20‐0.44, P 0.01).